O self dialógico no processo de amadurecimento do seminarista católico: uma ampliação para a prática psicoterapêutica desde uma perspectiva cultural da religião - Massih, Eliana (2012)
This thesis deals with a derivation of the Dialogic Self Theory in order to understand some psychotherapeutic issues on Catholic seminarians at the end of their personal training process. The life narratives, dreams, memories and reflections accounts of her clients are her main tools showing that dialogue established within the clinical conversations fosters the human adulthood. Some key concepts of this theory and the inclusion of some dimensions of the original culture of clients in the interpretation of clinical issues are the way used to reach that purpose. The author argues that her findings could be validated by the subjects of the research themselves; this is an appropriate way to investigate methodologically and epistemologically the human religiosity in its cultural dimension and, in particular, when one deals with subjects whose core value of their lives is the religiosity. As a last point, she validates her conclusions bringing up her own personal development as a researcher in Psychology of Religion and she proposes new research fields